Statements of Agreement From the Targeted Evaluation and Active Management (TEAM) Approaches to Treating Concussion Meeting Held in Pittsburgh, October 15-16, 2015. Issue 6 (12th October 2016) - Collins, Michael W.; Kontos, Anthony P.; Okonkwo, David O.; Almquist, Jon; Bailes, Julian; Barisa, Mark; Bazarian, Jeffrey; Bloom, O. Josh; Brody, David L.; Cantu, Robert; Cardenas, Javier; Clugston, Jay; et al.
Abstract: BACKGROUND: Conventional management for concussion involves prescribed rest and progressive return to activity. Recent evidence challenges this notion and suggests that active approaches may be effective for some patients. Previous concussion consensus statements provide limited guidance regarding active treatment. OBJECTIVE: To describe the current landscape of treatment for concussion and to provide summary agreements related to treatment to assist clinicians in the treatment of concussion. METHODS: On October 14 to 16, 2015, the Targeted Evaluation and Active Management (TEAM) Approaches to Treating Concussion meeting was convened in Pittsburgh, Pennsylvania. Thirty-seven concussion experts from neuropsychology, neurology, neurosurgery, sports medicine, physical medicine and rehabilitation, physical therapy, athletic training, and research and 12 individuals representing sport, military, and public health organizations attended the meeting. The 37 experts indicated their agreement on a series of statements using an audience response system clicker device. RESULTS: A total of 16 statements of agreement were supported covering (1) Summary of the Current Approach to Treating Concussion, (2) Heterogeneity and Evolving Clinical Profiles of Concussion, (3) TEAM Approach to Concussion Treatment: Specific Strategies, and (4) Future Directions: A Call to Research. Support (ie, response of agree or somewhat agree) for the statements ranged from to 97% to 100%. CONCLUSION: Concussions are characterized by diverse symptoms and impairments and evolving clinical profiles; recovery varies on the basis of modifying factors, injury severity, and treatments. Active and targeted treatments may enhance recovery after concussion. Research is needed on concussion clinical profiles, biomarkers, and the effectiveness and timing of treatments.